2020
DOI: 10.3233/trd-200048
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal imaging in urea cycle-related neurological disease – What can imaging after hyperammonemia teach us?

Abstract: BACKGROUND: Urea cycle-related brain disease may take on variable neuroimaging manifestations, ranging from normal to abnormal with or without a signature appearance. In the past, we have described the usefulness of multimodal imaging in identifying biomarkers of neuronal injury in UCD patients. In this study, we report unique findings in an adolescent male with neonatal-onset OTC deficiency after an episode of hyperammonemia. MATERIALS AND METHODS: Multiplanar, multisequence MR imaging (T1WI, T2WI, T2 FLAIR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Brain disorders related to UCDs may be evidenced by neuroimaging with manifestations ranging from normal to abnormal with or without a signature appearance. In recent years, it has been demonstrated that multimodal brain MRI using T1 weighted image, T2 weighted image, T2 fluid-attenuated inversion recovery, diffusion-weighted image, functional MRI, or/and 1 H/ 13 C magnetic resonance spectroscopy (MRS) is effective for the identification and evaluation of pathogenic neurologic conditions in patients with UCDs [ 37 ]. In patients with OTCD, even a partial or asymptomatic OTCD, 1 H MRS could detect increased glutamine levels, reduced myoinositol and choline levels in the brain, including frontal and parietal white matter, frontal gray matter, posterior cingulate gray matter, and thalamus [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brain disorders related to UCDs may be evidenced by neuroimaging with manifestations ranging from normal to abnormal with or without a signature appearance. In recent years, it has been demonstrated that multimodal brain MRI using T1 weighted image, T2 weighted image, T2 fluid-attenuated inversion recovery, diffusion-weighted image, functional MRI, or/and 1 H/ 13 C magnetic resonance spectroscopy (MRS) is effective for the identification and evaluation of pathogenic neurologic conditions in patients with UCDs [ 37 ]. In patients with OTCD, even a partial or asymptomatic OTCD, 1 H MRS could detect increased glutamine levels, reduced myoinositol and choline levels in the brain, including frontal and parietal white matter, frontal gray matter, posterior cingulate gray matter, and thalamus [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other MRI findings may include signal intensity increase in the regions of frontal lobes, cingulate gyri, temporal lobes, as well as the insular regions ( 60 ). Many patients may have a normal MRI with changes that appear after an acute hyperammonemic episode ( 61 ).…”
Section: Current Imaging Modalities In Ucdmentioning
confidence: 99%
“…Early in the course of HA, the MRI may be normal, and the only abnormal finding may be an elevated glutamine peak (gln) on MRS. MRS can detect elevated brain gln levels that is helpful in detection of subtle variations in OTCD females ( 59 ). Early diagnosis is critical to instituting ammonia lowering therapies, thus where available, 1HMRS adds typically 5–10 extra min to conventional MRI and can help in expediting diagnosis for partial or atypical OTCD when biochemical and molecular confirmation can take up to several days and weeks, respectively, and provides complementary information that can lead to early diagnosis ( 61 ) ( Figure 2 ). At our institution, modern neuroimaging techniques play a role in clinical monitoring and clinical decision making.…”
Section: Current Imaging Modalities In Ucdmentioning
confidence: 99%
See 1 more Smart Citation
“…Ornithine transcarbamylase deficiency (OTCD) is an X-linked inborn error of metabolism and the most common of the urea cycle disorders ( 1 ). Deficient protein metabolism in OTCD results in hyperammonemia (HA) that, in turn, disrupts the neurocognitive function in domains of working memory and executive function in several brain regions, including prefrontal cortex (PFC) ( 2 4 ). Investigation of neurocognitive function in working memory domain can become critical to understand the underlying effects of hyperammonemia in patients with OTCD.…”
Section: Introductionmentioning
confidence: 99%